The Simplified Thrombo-Inflammatory Score as a Novel Predictor of All-Cause Mortality in Patients with Heart Failure: A Retrospective Cohort Study - Cheng MD; Zheng YY; Zhang XY; Ruzeguli T; Sureya Y; Didaer Y; Ailiman M; Zhang JY (Dove Medical Press, 2024)
Meng-Die Cheng,1 Ying-Ying Zheng,2 Xing-Yan Zhang,2 Tuersun Ruzeguli,2 Yisimayili Sureya,2 Yisha Didaer,2 Mahemuti Ailiman,2 Jin-Ying Zhang1 1Department of Cardiology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450052, People's Republic of China; 2Department of Cardiology, The First Affiliated Hospital of Xinjiang Medical University, Urumqi, 830054, People's Republic of ChinaCorrespondence: Jin-Ying Zhang, Department of Cardiology, The First Affiliated Hospital of Zhengzhou University, No. 1, Jianshe Road, Zhengzhou, People's Republic of China, Tel +86-0371- 67967641, Email jyzhang@zzu.edu.cn Ying-Ying Zheng, Department of Cardiology, The First Affiliated Hospital of Xinjiang Medical University, No. 137, Liyushan Road, Urumqi, People's Republic of China, Tel +86-0991-4361702, Email zhengying527@163.comBackground: The simplified thrombo-inflammatory score (sTIPS) has recently emerged as a novel prognostic score. Hence, we investigated the prognostic value of sTIPS for predicting long-term mortality in patients with heart failure (HF).Methods: A total of 3741 patients were analyzed in this study. The sTIPS was calculated based on the white blood cell count (WBC) and the mean platelet volume to platelet count (MPV/PC) ratio at admission. The mean follow-up time was 22.75 months. Multivariable Cox regression analyses were used to investigate the associations between the sTIPS and all-cause mortality (ACM).Results: In the whole study population, multivariate Cox regression analysis showed that patients in both the sTIPS 2 and sTIPS 1 groups had significantly increased risk of ACM as compared with patients in the sTIPS 0 group (hazard ratio [HR]=1.706, 95% confidence interval [CI]: 1.405- 2.072, P< 0.001 and HR = 1.431, 95% CI 1.270- 1.612, P< 0.001). The same significant trend was observed in heart failure with preserved ejection fraction (HFpEF) patients (sTIPS1 vs sTIPS0: HR = 1.366, 95% CI 1.100- 1.697, P = 0.005; sTIPS2 vs sTIPS0: HR = 1.995, 95% CI 1.460- 2.725, P< 0.001). However, only sTIPS 1 group had a significantly increased the risk of ACM compared to the sTIPS 0 group among patients with HFmrEF (sTIPS1 vs sTIPS0: HR = 1.648, 95% CI 1.238- 2.194, P = 0.001) and HFrEF (sTIPS1 vs sTIPS0: HR = 1.322, 95% CI 1.021- 1.712, P = 0.035).Conclusion: sTIPS is useful in predicting risk for long-term mortality in patients with HF.Keywords: simplified thrombo-inflammatory score, heart failure, prognosis, all-cause mortality